Analysis of Prefixes in the Novel Always Forever Maybe - Kurniawati Lumintang; Ida Bagus Gde Nova Winarta (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This study investigated the semantic functions of English prefixation in Anica Mrose Rissi’s novel Always Forever Maybe. It employed a qualitative descriptive approach and analyzed five prefixed lexical items (rename, disintegrate, overblown, Outbid, and unintelligible) to examine how prefixation contributed to emotional tone, character development, and thematic depth. Data were gathered through close reading and were analysed morphologically using the frameworks of Katamba (1993) and Lieber (2009). In addition, the data were analysed by using a combination of labelled analysis, bracketing, and tree diagram techniques. The findings revealed that prefixes functioned as semantic modifiers without altering the grammatical class of the base words. They fulfilled conceptual roles such as reversal, directionality, intensity, and spatial relation. Unlike previous studies that addressed affixation more broadly, this research offered a focused perspective on the narrative utility of prefixation in literary discourse. The analysis of these prefixed words revealed that they serve as subtle yet impactful linguistic tools, enhancing literary expression by adding layers of meaning to the narrative, deepening character portrayals, and enriching thematic resonance. The study concludes that prefixation is a significant contributor to the overall literary and emotional impact of the novel.